Relationships Between Markers of Iron Status and Hematological Parameters in Patients With Sickle Cell Disease - Nermi L. Parrow; Jason M. Doherty; Anna Conrey; Swee Lay Thein; Robert E. Fleming (Advances in Hematology)
Based on the relationship between the intracellular concentration of sickle hemoglobin S (HbS) and the delay that occurs prior to the onset of sickling following deoxygenation, targeting the intracellular HbS concentration is a recognized therapeutic approach for sickle cell disease (SCD). We and others have shown that restricting iron by dietary or pharmacologic means improves hematologic parameters, inflammation, and organ damage in mouse models of SCD. Clinical evidence corroborating these findings is confined to case reports and small case series studies, none of which account for treatment or α-thalassemia. We hypothesize that increased transferrin saturation is associated with increased mean cellular hemoglobin concentration (MCHC) which in turn is associated with decreased red cell counts and worsening anemia. To investigate this hypothesis, we examined the relationships between transferrin saturation and MCHC with each of the parameters that define MCHC in sickle patients (HbSS without α-thalassemia) and healthy volunteers (HVs). Results indicate that transferrin saturation and MCHC are positively correlated with each other in sickle patients and HV. In patients with SCD, MCHC and transferrin saturation are negatively correlated with RBC count and are not correlated with hemoglobin, whereas each is positively associated with HV. Transferrin saturation and MCHC are each positively correlated with the hemolysis marker, lactate dehydrogenase. These observations support a model where increased transferrin saturation contributes to higher intracellular HbS concentrations with subsequent increases in sickling and hemolysis in sickle patients, suggesting that pharmacologic approaches to decrease serum iron may provide a therapeutic approach for patients with SCD.